Predictors of Participation in Voluntary Vocational Training: An Empirical Study among Canadian Female and Male Managers - Cloutier, Julie; Renaud, Stéphane; Morin, Lucie (Relations industrielles / Industrial Relations, 2008)
AbstractUsing Canadian national data from the Workplace and Employee Survey (WES), this study aims to identify predictors of participation in voluntary vocational training for female and male managers, respectively. Results show a higher rate of participation for female managers and a differential effect of predictors by gender. For men, schooling is the sole human capital variable significantly linked to the probability of participating in voluntary vocational training. For women, the probability of participating in voluntary vocational training varies by age, organizational tenure and schooling. Results also indicate that both participation in mandatory training and family responsibilities are significantly and negatively linked to participation in voluntary training for female managers but not for male managers.